Profitabilitas, Leverage, dan Likuiditas Terhadap Financial Distress pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Siti Muntahanah; Novanda Nur Huda; Endang Sri Wahyuningsih (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study is entitled "The Effect of Profitability, Leverage and Liquidity on Financial Distress in Consumer Goods Companies Listed on the Indonesia Stock Exchange". This research aimed to determine the effect simultaneously and partially of profitability, leverage, and liquidity towards financial distress on consumer goods companies listed on the Indonesia Stock Exchange. Samples were obtained based on a purposive sampling technique, and acquired 13 companies. The results obtained from the study are that profitability has a positive and significant effect on financial distress, leverage has a positive and significant effect on financial distress, and liquidity has a negative and significant effect on financial distress.